The Limits to Capital - Harvey, David (New York Verso, 2006)
The Limits to Capital provides one of the best theoretical guides to the history and geography of capitalist development. In this new edition, Harvey updates his classic text with a substantial discussion of the turmoil in world markets today.
Includes bibliographical references (p. [452]-465) and indexes.
Keywords: Capitalism